Feasibility study analysis of plantable seed paper packaging business based on palm oil fruit waste at PT. Growvi Indonesia - Andri Putra Arta; Dina Arfianti Saragih (Indonesia Auditing Research Journal, 2026)
This study aims to analyze the feasibility of PT Growvi Indonesia's plantable seed paper and paper bag products made from oil palm fronds. The method used is descriptive quantitative, with primary and secondary data obtained through observation, interviews, documentation, and literature review. The analysis covered market, technical and operational, managerial and legal, financial, and environmental and social aspects. The results indicate that the business has good prospects, with broad market potential and abundant raw material availability. Financially, the business is deemed feasible based on a positive NPV, high IRR, Net B/C greater than one, and a short payback period. Furthermore, the business has a positive environmental impact through the utilization of oil palm waste. In conclusion, PT Growvi Indonesia is feasible to expand by increasing production capacity and strengthening marketing strategies to support business sustainability.